Morphological ontogeny of Galumna flagellata Willmann (Acari: Oribatida: Galumnidae). Issue 3 (3rd April 2021) - Seniczak, Anna; Seniczak, Stanisław; Rodríguez-Fernández, Sofía; Fernandez Ondoño, Emilia
ABSTRACT: The morphological ontogeny of Galumna flagellata Willmann, 1925 is described and illustrated. The juveniles of this species are light brown, with prodorsal setae of medium size or long and barbed, and bothridial seta clavate. The larva has 12 pairs of gastronotal setae, most of the medium size and barbed, of which seven ( d-, l -series, h 1 ) are located on gastronotal shield, nymphs have 15 pairs, mostly short setae, of which 10 ( d-, l-, h -series, p 1 ) are located on the gastronotal shield, setae of c -series are inserted on individual sclerites. In all juveniles, the typical galumnid humeral organ is absent, but a porose area is present in this location, which is unique in Galumna .